Effect of Number of Various-Type Acid Sites Located on 20 % Co/ZrO2 • SiO2 Sample Surface on Parameters of Catalytic Process in Synthesis of High-Octane Motor Fuel Components - A. P. Nesenchouk; A. V. Sednin; O. F. Kraetskaya; L. M. Sliapniova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers an effect of ZrO2 content in 20%Co/xZrO2∙(100 – x)SiO2 (x = 0, 10, 15, 25, 30, 40 and 100 mass percent) catalyst carriers on their catalytic properties. Temperature programmed desorption of NH3 has made it possible to determine relations between their acid and catalytic properties. The paper reveals the TPD spectrum is the result of 4 overlapping peaks originating during NH3 desorption from the respective groups of acid sites. Total acidity of samples and contribution of separate acid site groups into the given acidity have been have been determined in the paper. The paper contains graphical dependences of a various-type acid site number on  content of zirconium oxide in the carrier. Correlations between change in various-type acid site number and catalytic process parameters (CO conversion, C5+ hydrocarbon output and  C5+ isoparaffin output) have been found in the paper. The paper shows that the highest values of CO conversion and C5+ hydrocarbon output correspond to maximum number of acid sites, and that number accounts for a peak of desorbed ammonia at Tmax = 122 °C, while the lowest isoparaffin output corresponds to minimum number of acid sites, which characterizes a peak of desorbed ammonia at Tmax = 224–257 °C.